Identifikasi Uji Mutu Dan Sensori Kopi Bubuk - Nur Janah; Enny Purwati Nurlaili; Ali Umar Dhani (Jurnal Agrifoodtech, 2023)
Coffe is one the plantation commodities that has high economic value and plays an important role as a source of foreign exchange for the country. The purpose of this study was to examine the quality test, tp determine whether there was a difference and to determine the content of water content, ash, alkalinity of the ash, coffee extract, caffeine and mineral Zinc (Zn) as well as the sensory test on ground coffe that met the requirements based on SNI 01-3542-2004. This research consisted of two research phases, namely research phase I, sample selection phase and research phase II, chemical test phase and sensory test. The research method used a completely randomized design (CRD) with 3 treatments and 3 replications. The research treatments included factory ground coffee (A), ground coffee from the Mranggen market area (D), ground coffee from the Mrican market area (E). If there is a significant difference, the Duncans Multiple Range Test (DMRT) test is carried out. The results of the first stage of the research, the sample selection stage, from five variants of factory ground coffee (brands A, B, C, F, G) after a sensory test were selected, factory ground coffee (brand A) was used as research material. From this sample selection stage, 3 ground coffee samples were obtained, namely factory ground coffee (A), ground coffee from the Mranggen market area (D coffee powder), and ground coffee from the Mrican market area (E powder coffee). The results of the hedonic test of taste parameters showed that ground coffee which had the highest preference value for taste was ground coffee with treatment A (4.47) which means like. The results of the second stage of the research on the analysis of the chemical properties of treatment A, water content (2.56%), ash content (4.48%), ash alkalinity (63.15 ml x n.NaOH/100 g), coffee extract (21.13%), caffeine (2.07% ), Zn (10.06 mg/kg). Treatment D, water content (5.60%), ash content (2.82%), alkalinity of ash (58.18 ml x n.NaOH/100 g), coffee extract (14.88%), caffeine (1.86%), Zn (19.47 mg/kg ). Treatment E, moisture content (6.17%), ash content (2.54%), ash alkalinity (48.28 ml x n.NaOH/100 g), coffee extract (10.61%), caffeine (1.48%), Zn (18.47 mg/kg ) in the sensory test hedonic test panelists liked treatment A (4.07) which means like, aroma A (4.73) which means very like, and taste A (4.73) which means very like. The conclusion of the study showed that the presence of , differences in water content, ash, alkalinity of ash, coffee extract, caffeine and the mineral Zinc (Zn) as well as a sensory test using the affective test method (acceptance test) including hedonic tests affected the sensory properties of ground coffee and met the quality characteristics according to SNI 01-3542-2004.